Adenoviral production of interleukin‐2 at the tumor site removes the need for systemic postconditioning in adoptive cell therapy. Issue 7 (29th June 2017) - Santos, Joao Manuel; Havunen, Riikka; Siurala, Mikko; Cervera‐Carrascon, Víctor; Tähtinen, Siri; Sorsa, Suvi; Anttila, Marjukka; Karell, Pauliina; Kanerva, Anna; Hemminki, Akseli
Abstract : Systemic high dose interleukin‐2 (IL‐2) postconditioning has long been utilized in boosting the efficacy of T cells in adoptive cell therapy (ACT) of solid tumors. The resulting severe off‐target toxicity of these regimens renders local production at the tumor an attractive concept with possible safety gains. We evaluated the efficacy and safety of intratumorally administered IL‐2‐coding adenoviruses in combination with tumor‐infiltrating lymphocyte therapy in syngeneic Syrian hamsters bearing HapT1 pancreatic tumors and with T cell receptor transgenic ACT in B16.OVA melanoma bearing C57BL/6 mice. The models are complementary: hamsters are semi‐permissive for human oncolytic adenovirus, whereas detailed immunological analyses are possible in mice. In both models, local production of IL‐2 successfully replaced the need for systemic recombinant IL‐2 (rIL‐2) administration and increased the efficacy of the cell therapy. Furthermore, vectored delivery of IL‐2 significantly enhanced the infiltration of CD8+ T cells, M1‐like macrophages, and B‐cells while systemic rIL‐2 increased CD25 + FoxP3+ T cells at the tumor. In contrast with vectored delivery, histopathological analysis of systemic rIL‐2‐treated animals revealed significant changes in lungs, livers, hearts, spleens, and kidneys. In summary, local IL‐2 production results in efficacy and safety gains in the context of ACT. These preclinical assessments provide the rationale for ongoing clinical translation. Abstract : Whart's new? While cancer immunotherapy with tumor‐infiltrating lymphocytes is promising, the systemic application of high doses of interleukin‐2 (IL‐2) necessary for lymphocyte proliferation in solid tumors is often highly toxic. Here, the authors show that tumor‐selective production of IL‐2 from an oncolytic adenovirus successfully replaced the systemic application and improved the efficacy and safety of adoptive cell therapy in two complementary animal models. These results form the basis for a phase I clinical trial in melanoma patients.